Preparation method of super-hydrophobic composite coating based on magnetically-induced fluorinated graphene
By loading magnetic nanoparticles between the fluorinated graphene sheets and using an external magnetic field to move them directionally to the coating surface, a superhydrophobic composite coating is prepared, which solves the problems of poor mechanical stability and complex process of the existing coating, and realizes the coating performance with multiple functions.
Patent Information
- Application Number
- CN202411703963.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
AI Technical Summary
The existing super-hydrophobic, anti-corrosion and anti-fouling coatings have poor mechanical stability, complex processes and poor economical practicality, making it difficult to meet the industrial needs of marine engineering equipment and oil and gas development platforms.
The magnetic nanoparticles were loaded between the fluorinated graphene sheets that were dispersed with low temperature ultrasonic by thermal solvent method, and magnetic nanoparticles-fluorinated graphene composite materials were obtained by magnetic separation and freeze-drying. The coating was prepared and moved directionally to the coating surface under the induced external magnetic field to form a superhydrophobic composite coating.
It improves the dispersion of fluorinated graphene and the corrosion resistance of the coating, and realizes multiple functions of super-hydrophobic, anti-corrosion and anti-fouling. It has simple process, environmental protection, low cost, and is suitable for large-scale production.
Smart Images

Figure CN119529587A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional coating preparation, and in particular relates to a method for preparing a super-hydrophobic composite coating based on magnetically induced fluorinated graphene. Background Art
[0002] my country has made remarkable progress in the field of deep-sea resource development, and has achieved major breakthroughs in deep-sea oil and gas development and marine engineering equipment manufacturing technology. Deep-sea marine engineering equipment and oil and gas development platforms are in extremely corrosive environments such as high humidity, high salinity, and long sunshine. At the same time, they are subject to natural loads such as waves, typhoons, sea ice, and biological attachment and fouling. The coupling of multiple complex environments poses a serious threat to the safe operation of marine engineering equipment and oil and gas development platforms. Therefore, it is necessary to take effective anti-corrosion and anti-fouling measures to extend the service life of marine engineering equipment and oil and gas development platforms.
[0003] Nowadays, coating technology is mainly used to protect marine engineering equipment and oil and gas development platforms, prevent, reduce or control the corrosion and pollution of marine engineering equipment and oil and gas development platforms. Among them, super-hydrophobic coating has become the main coating protection technology for marine engineering equipment and oil and gas development platforms because of its excellent self-cleaning performance, resistance to environmental corrosion and resistance to marine biological fouling. Super-hydrophobic coating has good anti-wetting properties, and the rough microscopic surface structure can form a layer of air protection film, which effectively isolates the corrosive media in humid air and seawater, effectively improves the anti-corrosion performance, inhibits the adhesion of fouling organisms through the self-cleaning effect (low surface energy), and enhances the anti-fouling effect of the coating.
[0004] However, the existing super-hydrophobic, anti-corrosion and anti-fouling coatings have poor mechanical stability, are easily damaged, and have complex process engineering and poor economic practicability. Chinese patent CN 112409884 A discloses a method for preparing an epoxy resin / GO super-hydrophobic anti-corrosion coating, wherein the surface of the nano GO-Fe3O4 composite material is first amino-modified, the curing agent is fluorinated, and then the coating surface is hydrophobized by hydrolysis of fluorosilane, and the process is complicated and cumbersome, and it is difficult to meet the needs of industrialization. Therefore, it is of great significance to develop a super-hydrophobic, anti-corrosion and anti-fouling coating with high mechanical stability and good economic practicability to extend the service life of marine engineering equipment and oil and gas development platforms. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a super-hydrophobic composite coating based on magnetically induced fluorinated graphene.
[0006] The method for preparing a super-hydrophobic composite coating based on magnetically induced fluorinated graphene according to the present invention comprises the following steps:
[0007] The magnetic nanoparticles are loaded between the fluorinated graphene sheets dispersed by low temperature ultrasonic dispersion by a hot solvent method, and the reaction product is subjected to magnetic separation and freeze drying to obtain a magnetic nanoparticle-fluorinated graphene composite material;
[0008] The coating is prepared using a magnetic nanoparticle-fluorinated graphene composite material;
[0009] After the coating is applied to the surface of the substrate, a directional magnetic field of a certain magnetic field strength is applied to the coating substrate to make the magnetic nanoparticle-fluorinated graphene composite material move to the coating surface in a directional manner to obtain a super-hydrophobic composite coating.
[0010] Compared with the prior art, the super-hydrophobic composite coating based on magnetically induced fluorinated graphene provided by the present invention, first under low-temperature ultrasonic conditions, the reactants of fluorinated graphene with high fluorine content and magnetic nanoparticles are uniformly dispersed, and then the magnetic nanoparticles are loaded between the dispersed fluorinated graphene sheets by a hot solvent method, and then the reaction product is magnetically separated and freeze-dried to obtain a magnetic nanoparticle-fluorinated graphene composite material, a coating is prepared based on the composite material and applied to the surface of the substrate, and under the precise induction of an external magnetic field, the magnetic nanoparticle-fluorinated graphene composite material in the coating moves directional to the coating surface, forming a super-hydrophobic composite coating with a microscopic rough structure and low surface energy characteristics on the surface. The present invention peels off fluorinated graphene by anchoring magnetic nanoparticles between fluorinated graphene sheets, effectively improving the agglomeration of fluorinated graphene and improving the dispersibility of fluorinated graphene in an organic resin matrix; using the unique lamellar structure of fluorinated graphene, it is possible to effectively delay the diffusion of corrosive media into the coating and enhance the corrosion resistance of the coating. The coating prepared by the present invention integrates multiple functions such as hydrophobicity, corrosion resistance and antifouling, can show excellent performance in a variety of environments, meet the needs of different application scenarios, and can be applied to a variety of different substrate surfaces to achieve super hydrophobicity, corrosion resistance and antifouling effects; and the process for preparing the composite coating is simple, environmentally friendly and pollution-free, low-cost, and can be used for mass production.
[0011] Furthermore, the fluorine content of the fluorinated graphene is greater than or equal to 50%.
[0012] Furthermore, the magnetic nanoparticles are one or more of magnetite (Fe3O4), nano zero-valent iron (nZVI), magnetic hematite (γ-Fe2O3), hematite (α-Fe2O3), Fe / Fe3O4 nanoparticles, and metal-doped iron oxides.
[0013] Further, the freeze-drying comprises the following steps:
[0014] The reaction product separated by magnetic separation is placed in liquid nitrogen and frozen for 15 to 25 minutes;
[0015] The reaction product frozen by liquid nitrogen is placed in a freeze drying oven for freeze drying for 24 h to 48 h, wherein the freezing temperature is controlled at -40°C.
[0016] Further, preparing the coating comprises the following steps:
[0017] ultrasonically dispersing the magnetic nanoparticle-fluorinated graphene composite material in a solvent to form a uniform suspension;
[0018] Resin is added to the suspension and mixed evenly, and then a curing agent is added and stirred evenly, and vacuum degassing and defoaming are performed to obtain a coating mixture.
[0019] Furthermore, the mass percentage of the magnetic nanoparticle-fluorinated graphene composite material in the resin matrix is 7wt% to 15wt%.
[0020] Furthermore, the resin is one or more of epoxy resin, fluorocarbon resin, acrylic resin, silicone resin, acrylic modified silicone resin, acrylic modified polyurethane resin, fluorosilicone resin, and polyvinylidene fluoride; and the curing agent is one or more of amines and isocyanates.
[0021] Furthermore, the magnetic nanoparticles are magnetite (Fe3O4), and the magnetic Fe3O4 nanoparticle-fluorinated graphene composite material is prepared by the following steps:
[0022] Dispersing the fluorinated graphene in a solvent, and ultrasonically dispersing it in an ice-water bath to form a uniform dispersion;
[0023] adding iron (III) chloride hexahydrate to the dispersion, and continuing to ultrasonically disperse in an ice-water bath to dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion;
[0024] Adding a reducing agent, a stabilizer and a surfactant to the iron (III) chloride hexahydrate-graphene fluoride dispersion in sequence, stirring and mixing evenly to form a mixed solution;
[0025] The mixed solution is transferred into a high-pressure reactor for hydrothermal reaction. After the reaction is completed, the reaction product is subjected to magnetic separation and repeatedly washed and separated with anhydrous ethanol;
[0026] The reaction product after magnetic separation is freeze-dried to obtain a composite material of magnetic Fe3O4 nanoparticles partially coated with fluorinated graphene.
[0027] Furthermore, the reducing agent and the stabilizing agent are one or more of anhydrous sodium acetate, anhydrous ammonium acetate, sodium citrate, and ascorbic acid; the surfactant is polyethylene glycol of different molecular weights, specifically one or more of Mn 2000, Mn 6000, Mn 4000, Mn 1000, and Mn 8000.
[0028] Furthermore, the hydrothermal reaction temperature is 200° C. to 220° C., and the reaction time is 24 h to 70 h.
[0029] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A schematic diagram of a preparation process according to an embodiment of the present invention;
[0031] Figure 2 This is a SEM image of the magnetic nanoparticle-fluorinated graphene composite material prepared in the present invention;
[0032] Figure 3 TEM image of the magnetic nanoparticle-fluorinated graphene composite material prepared by the present invention;
[0033] Figure 4 The figure is a test result diagram of magnetic adsorption and hydrophobicity of the magnetic nanoparticle-fluorinated graphene composite material prepared by the present invention;
[0034] Figure 5 A graph showing the hydrophobicity test results of the super-hydrophobic composite coating based on magnetically induced fluorinated graphene prepared by the present invention. DETAILED DESCRIPTION
[0035] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0036] The carbon atoms and fluorine atoms in fluorinated graphene are combined by covalent bonds to form a two-dimensional graphene derivative, which retains the unique two-dimensional layered structure of graphene. Due to the existence of CF bonds, it has special properties such as low surface energy, strong hydrophobicity, high insulation, friction resistance, corrosion resistance and high temperature resistance. It has great application potential in the fields of functional coatings such as high temperature resistance, super hydrophobicity, wear resistance and corrosion resistance. However, the low surface energy of fluorinated graphene and the strong van der Waals force between its sheets make it very easy for the fluorinated graphene sheets to agglomerate, resulting in poor dispersion of fluorinated graphene in the coating.
[0037] In order to solve the problem of poor dispersibility of fluorinated graphene in the coating, the present invention studies a preparation method of a super-hydrophobic composite coating based on magnetically induced fluorinated graphene, wherein the preparation method first partially encapsulates the fluorinated graphene in magnetic nanoparticles to form a magnetic nanoparticle-fluorinated graphene composite material; then, by setting a magnetic field outside the coating, the magnetic nanoparticle-fluorinated graphene composite material is directed to move toward the coating surface under the precise induction of the external magnetic field, and is evenly distributed on the coating surface along the magnetic field lines to form a composite coating with a microscopic roughness on the surface. Encapsulating the fluorinated graphene partially in magnetic nanoparticles can effectively improve the agglomeration between fluorinated graphene sheets and improve its dispersibility in the coating; at the same time, the fluorinated graphene is given good magnetic properties, and the fluorinated graphene is evenly distributed on the coating surface through magnetic induction. With the hydrophobic properties of the fluorinated graphene, the composite coating is super-hydrophobic, anti-corrosive and anti-fouling.
[0038] See also Figure 1 and Figure 2 The preparation method of the super-hydrophobic composite coating based on magnetically induced fluorinated graphene of the present application is described in detail below, including the following steps.
[0039] (I) Preparation of magnetic nanoparticle-fluorinated graphene composites
[0040] The magnetic nanoparticles are loaded between the fluorinated graphene sheets dispersed by low-temperature ultrasonic dispersion by a hot solvent method, and the reaction product is subjected to magnetic separation and freeze-drying to obtain a magnetic nanoparticle-fluorinated graphene composite material.
[0041] The fluorinated graphene is highly fluorinated graphene with a fluorine content of more than 50%.
[0042] The magnetic nanoparticles can be one or more of magnetite (Fe3O4), nano zero-valent iron (nZVI), magnetic hematite (γ-Fe2O3), hematite (α-Fe2O3), Fe / Fe3O4 nanoparticles, and metal-doped iron oxides (such as MnFe2O4, FeFe2O4, CoFe2O4, and NiFe2O4, etc.). The above magnetic nanoparticles are all prepared by a hot solvent method. Specifically, under low-temperature ultrasonic conditions, the reactants of fluorinated graphene with a high fluorine content and magnetic nanoparticles are uniformly dispersed, and then the magnetic nanoparticles are loaded between the fluorinated graphene sheets by a hot solvent method.
[0043] Taking the loading of magnetic Fe3O4 nanoparticles between fluorinated graphene sheets as an example, the specific preparation steps are as follows:
[0044] 1.1 Dispersing fluorinated graphene FG in a solvent, and ultrasonically dispersing in an ice-water bath to form a uniform dispersion, wherein the solvent is ethylene glycol;
[0045] 1.2 Adding iron (III) chloride hexahydrate to the dispersion, and continuing to ultrasonically disperse in an ice-water bath to dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion;
[0046] 1.3 Add a reducing agent, a stabilizer and a surfactant to the iron (III) chloride hexahydrate-graphene fluoride dispersion in sequence, stir and mix evenly to form a mixed solution, wherein the reducing agent and the stabilizer specifically refer to one or more of anhydrous sodium acetate, anhydrous ammonium acetate, sodium citrate, and ascorbic acid, and the surfactant specifically refers to polyethylene glycol of different molecular weights, specifically one or more of Mn 2000, Mn 6000, Mn 4000, Mn 1000, and Mn 8000;
[0047] 1.4 The mixed solution is transferred into a high-pressure reactor for hydrothermal reaction. After the reaction is completed, the reaction product is subjected to magnetic separation and repeatedly washed and separated with anhydrous ethanol. The hydrothermal reaction temperature is 200°C to 220°C and the reaction time is 24h to 70h.
[0048] 1.5 The reaction product after magnetic separation is freeze-dried to obtain a magnetic Fe3O4 nanoparticle partially coated with a fluorinated graphene composite material (Fe3O4@FG), wherein the freeze-drying process comprises: freezing the reaction product after magnetic separation in liquid nitrogen for 15 min to 25 min; placing the reaction product frozen by liquid nitrogen in a freeze drying box for freeze drying for 24 h to 48 h, wherein the freezing temperature is controlled at -40°C.
[0049] (II) Preparation of super-hydrophobic composite coating
[0050] The coating is prepared by using a magnetic nanoparticle-fluorinated graphene composite material. After the coating is applied to the surface of a substrate, a directional magnetic field of a certain magnetic field strength is applied to the coating substrate to make the magnetic nanoparticle-fluorinated graphene composite material move to the coating surface in a directional manner to obtain a super-hydrophobic composite coating. The specific preparation steps are as follows:
[0051] 2.1 ultrasonically dispersing the magnetic nanoparticle-fluorinated graphene composite material in a solvent to form a uniform suspension, wherein the solvent is one or more of ethanol, ethylene glycol, xylene, butyl acetate and ethyl acetate;
[0052] 2.2 Add resin to the suspension and mix evenly, then add curing agent and stir evenly, and perform vacuum degassing and defoaming to obtain a coating mixture, wherein the mass percentage of magnetic nanoparticle-fluorinated graphene composite material in the resin matrix is 7wt%-15wt%; the resin specifically refers to one or more of epoxy resin, fluorocarbon resin, acrylic resin, silicone resin, acrylic modified silicone resin, acrylic modified polyurethane resin, fluorosilicone resin, polyvinylidene fluoride, and is not limited thereto; the curing agent specifically refers to one or more of amine and isocyanate curing agents, and is not limited thereto;
[0053] 2.3 The treated metal substrate surface is evenly coated by spraying. During the curing film formation process, a directional magnetic field of a certain magnetic field strength is applied to the surface of the coating substrate to induce the magnetic nanoparticle-fluorinated graphene composite material to migrate toward the coating surface, thereby forming a super-hydrophobic composite coating with a rough surface structure.
[0054] The technical scheme and technical effects of the present invention are further described below in conjunction with embodiments and comparative examples.
[0055] It should be noted that the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] In this embodiment, a super-hydrophobic composite coating based on magnetically induced fluorinated graphene is prepared according to the following method.
[0058] (I) Preparation of Fe3O4 nanoparticle-fluorinated graphene composites
[0059] 1.1 Disperse 0.2 g of fluorinated graphene (FG) with a fluorine content of 50% in ethylene glycol and ultrasonically disperse it in an ice-water bath for 30 min to form a uniform dispersion;
[0060] 1.2 Add 1.35 g of iron (III) chloride hexahydrate to the dispersion, and continue to disperse by ultrasonic in an ice-water bath to completely dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion;
[0061] 1.3 Then, 3.6 g of anhydrous sodium acetate and 1.0 g of polyethylene glycol (Mn2000) were added to the iron (III) chloride hexahydrate-fluorinated graphene dispersion in sequence, and the mixture was stirred and mixed to form a mixed solution;
[0062] 1.4 The mixed solution was transferred into a high pressure reactor for hydrothermal reaction at 200°C for 24 hours. After the reaction was completed, the reaction product was subjected to magnetic separation and repeatedly washed and magnetically separated with anhydrous ethanol;
[0063] 1.5 The reaction product after magnetic separation was frozen in liquid nitrogen for 15 minutes, and then placed in a freeze drying oven at -40°C for 24 hours to obtain a Fe3O4 nanoparticle-fluorinated graphene (Fe3O4@FG) composite material.
[0064] (II) Preparation of super-hydrophobic composite coating
[0065] 2.1 10wt% Fe3O4@FG composite material was ultrasonically dispersed in ethanol solution to form a uniform suspension;
[0066] 2.2 Add epoxy resin emulsion to the suspension and mix evenly, then add curing agent and stir evenly, and perform vacuum degassing and defoaming to obtain a coating mixture;
[0067] 2.3 The coating mixture is evenly coated on the treated metal substrate surface by spraying. During the curing film formation process, an electromagnet is fixed 5 cm above the upper surface of the coating substrate and a magnetic field strength of 0.5 T is applied to induce the Fe3O4@FG composite material to migrate directional to the coating surface, forming a superhydrophobic composite coating with a rough surface structure.
[0068] Example 2
[0069] In this embodiment, a super-hydrophobic composite coating based on magnetically induced fluorinated graphene is prepared according to the following method.
[0070] (I) Preparation of Fe3O4 nanoparticle-fluorinated graphene composites
[0071] 1.1 0.3 g of fluorinated graphene (FG) with a fluorine content of 55% was dispersed in ethylene glycol and ultrasonically dispersed in an ice-water bath for 30 min to form a uniform dispersion;
[0072] 1.2 Add 1.35 g of iron (III) chloride hexahydrate to the dispersion, and continue to disperse by ultrasonic in an ice-water bath to completely dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion;
[0073] 1.3 Then, 3.6 g of anhydrous ammonium acetate and 1.0 g of polyethylene glycol (Mn4000) were added to the iron (III) chloride hexahydrate-fluorinated graphene dispersion in sequence, and the mixture was stirred and mixed to form a mixed solution;
[0074] 1.4 The mixed solution was transferred into a high pressure reactor for hydrothermal reaction at 200°C for 48 hours. After the reaction was completed, the reaction product was subjected to magnetic separation and repeatedly washed and magnetically separated with anhydrous ethanol;
[0075] 1.5 The reaction product after magnetic separation was frozen in liquid nitrogen for 15 minutes, and then placed in a freeze drying oven at -40°C for 24 hours to obtain a Fe3O4 nanoparticle-fluorinated graphene (Fe3O4@FG) composite material.
[0076] (II) Preparation of super-hydrophobic composite coating
[0077] 2.1 12wt% Fe3O4@FG composite material was ultrasonically dispersed in ethanol solution to form a uniform suspension;
[0078] 2.2 Add epoxy resin emulsion to the suspension and mix evenly, then add curing agent and stir evenly, and perform vacuum degassing and defoaming to obtain a coating mixture;
[0079] 2.3 The coating mixture is evenly coated on the treated metal substrate surface by spraying. During the curing film formation process, an electromagnet is fixed 5 cm above the upper surface of the coating substrate and a magnetic field strength of 0.4 T is applied to induce the Fe3O4@FG composite material to migrate directional to the coating surface, forming a super-hydrophobic composite coating with a rough surface structure.
[0080] Example 3
[0081] In this embodiment, a super-hydrophobic composite coating based on magnetically induced fluorinated graphene is prepared according to the following method.
[0082] (I) Preparation of Fe3O4 nanoparticle-fluorinated graphene composites
[0083] 1.1 0.35 g of fluorinated graphene (FG) with a fluorine content of 60% was dispersed in ethylene glycol and ultrasonically dispersed in an ice-water bath for 30 min to form a uniform dispersion;
[0084] 1.2 Add 1.35 g of iron (III) chloride hexahydrate to the dispersion, and continue to disperse by ultrasonic in an ice-water bath to completely dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion;
[0085] 1.3 Then, 3.6 g of anhydrous ammonium acetate and 1.0 g of polyethylene glycol (Mn6000) were added to the iron (III) chloride hexahydrate-fluorinated graphene dispersion in sequence, and the mixture was stirred and mixed to form a mixed solution;
[0086] 1.4 The mixed solution was transferred into a high pressure reactor for hydrothermal reaction at 200°C for 36 hours. After the reaction was completed, the reaction product was subjected to magnetic separation and repeatedly washed and magnetically separated with anhydrous ethanol;
[0087] 1.5 The reaction product after magnetic separation was frozen in liquid nitrogen for 15 minutes, and then placed in a freeze drying oven at -40°C for 24 hours to obtain a Fe3O4 nanoparticle-fluorinated graphene (Fe3O4@FG) composite material.
[0088] (II) Preparation of super-hydrophobic composite coating
[0089] 2.1 15wt% Fe3O4@FG composite material was ultrasonically dispersed in ethanol solution to form a uniform suspension;
[0090] 2.2 Add epoxy resin emulsion to the suspension and mix evenly, then add curing agent and stir evenly, and perform vacuum degassing and defoaming to obtain a coating mixture;
[0091] 2.3 The coating mixture is evenly coated on the treated metal substrate surface by spraying. During the curing film formation process, an electromagnet is fixed at 7 cm above the upper surface of the coating substrate and a magnetic field strength of 0.5 T is applied to induce the Fe3O4@FG composite material to migrate directional to the coating surface, forming a super-hydrophobic composite coating with a rough surface structure.
[0092] Comparative Example
[0093] This comparative example is a method for preparing a composite coating without loading magnetic nanoparticles on graphite fluoride, specifically, comprising the following steps:
[0094] 2.1 10 wt% of fluorinated graphene was ultrasonically dispersed in an ethanol solution to form a uniform suspension;
[0095] 2.2 Add epoxy resin emulsion to the suspension and mix evenly, then add curing agent and stir evenly, and perform vacuum degassing and defoaming to obtain a coating mixture;
[0096] 2.3 The coating mixture is evenly coated on the treated metal substrate surface by spraying. During the curing film formation process, an electromagnet is fixed at 7 cm above the upper surface of the coating substrate and a magnetic field strength of 0.5 T is applied to form a composite coating.
[0097] Results Test Analysis
[0098] Performance testing and analysis were performed on the super-hydrophobic composite coatings based on magnetically induced fluorinated graphene prepared in Examples 1 to 3 and the composite coating prepared in the comparative example.
[0099] Test environment conditions: temperature 20℃~25℃, relative humidity 50%~60%.
[0100] Test equipment and test conditions:
[0101] 1. Hydrophobicity (static water contact angle)
[0102] Testing equipment: contact angle tester;
[0103] Test conditions: Refer to standard GB / T 30447-2013 Nanofilm contact angle measurement method.
[0104] 2. Neutral salt spray resistance test
[0105] Test equipment: composite salt spray test chamber;
[0106] Test conditions: Refer to standard GB / T 1771-2007 Determination of neutral salt spray resistance of paints and varnishes.
[0107] 3. Anti-fouling and durable performance
[0108] Test equipment: Outdoor exposure test stand
[0109] Test conditions: GB / T 9276-1996 coating natural climate exposure test method
[0110] 4. Impact resistance
[0111] Test conditions: Reference standard GB / T 1732-2020 Determination of impact resistance of paint films.
[0112] The test results are as follows:
[0113] Table 1 Coating performance test results
[0114]
[0115] The performance characterization test results in Table 1 are analyzed: the coatings prepared in Examples 1 to 3 have a fluorinated graphene surface layer based on magnetic induction, and the static water contact angle thereof is 150° to 160°, which is much larger than 120° of the comparative example. It can be seen that the hydrophobicity of Examples 1 to 3 is better; for the tests of salt spray resistance and anti-fouling durability, it can also be concluded that the corrosion resistance and pollution resistance of Examples 1 to 3 are better; for impact resistance, the coating surfaces of Examples 1 to 3 are still not damaged under the experimental condition of a falling ball height of 50 cm, but the comparative example is damaged under the experimental condition of a falling ball height of 45 cm, which shows that the impact resistance of Examples 1 to 3 is better.
[0116] The above data show that the super-hydrophobic composite coating based on magnetically induced fluorinated graphene prepared by the present invention has better corrosion resistance, pollution resistance and impact resistance. The composite coating is applied to the surface of a substrate such as metal or ceramic to achieve super-hydrophobic, long-term corrosion and anti-fouling effects.
[0117] The present invention is not limited to the above-mentioned embodiments. If various changes or modifications to the present invention do not depart from the spirit and scope of the present invention, and if these changes and modifications fall within the scope of the claims and equivalent technologies of the present invention, the present invention is also intended to include these changes and modifications.
Claims
1. A method for preparing a super-hydrophobic composite coating based on magnetically induced fluorinated graphene, characterized in that: The steps include: The magnetic nanoparticles are loaded between the fluorinated graphene sheets dispersed by low temperature ultrasonic dispersion by a hot solvent method, and the reaction product is subjected to magnetic separation and freeze drying to obtain a magnetic nanoparticle-fluorinated graphene composite material; The coating is prepared using a magnetic nanoparticle-fluorinated graphene composite material; After the coating is applied to the surface of the substrate, a directional magnetic field of a certain magnetic field strength is applied to the coating substrate to make the magnetic nanoparticle-fluorinated graphene composite material move to the coating surface in a directional manner to obtain a super-hydrophobic composite coating.
2. The preparation method according to claim 1, characterized in that: The fluorine content of the fluorinated graphene is greater than or equal to 50%.
3. The preparation method according to claim 2, characterized in that: The magnetic nanoparticles are one or more of magnetite (Fe3O4), nano zero-valent iron (nZVI), magnetic hematite (γ-Fe2O3), hematite (α-Fe2O3), Fe / Fe3O4 nanoparticles, and metal-doped iron oxides.
4. The preparation method according to claim 3, characterized in that: The freeze drying comprises the following steps: The reaction product separated by magnetic separation is placed in liquid nitrogen and frozen for 15 to 25 minutes; The reaction product frozen by liquid nitrogen is placed in a freeze drying oven for freeze drying for 24 h to 48 h, wherein the freezing temperature is controlled at -40°C.
5. The preparation method according to claim 3, characterized in that: The preparation of the coating comprises the following steps: ultrasonically dispersing the magnetic nanoparticle-fluorinated graphene composite material in a solvent to form a uniform suspension; Resin is added to the suspension and mixed evenly, and then a curing agent is added and stirred evenly, and vacuum degassing and defoaming are performed to obtain a coating mixture.
6. The preparation method according to claim 5, characterized in that: The mass percentage of the magnetic nanoparticle-fluorinated graphene composite material to the resin matrix is 7wt% to 15wt%.
7. The preparation method according to claim 5 or 6, characterized in that: The resin is one or more of epoxy resin, fluorocarbon resin, acrylic resin, silicone resin, acrylic modified silicone resin, acrylic modified polyurethane resin, fluorosilicone resin, and polyvinylidene fluoride; the curing agent is one or more of amines and isocyanates.
8. The preparation method according to any one of claims 3, 4, 5 and 7, characterized in that: The magnetic nanoparticles are magnetite (Fe3O4), and the magnetic Fe3O4 nanoparticle-fluorinated graphene composite material is prepared by the following steps: Dispersing the fluorinated graphene in a solvent, and ultrasonically dispersing it in an ice-water bath to form a uniform dispersion; adding iron (III) chloride hexahydrate to the dispersion, and continuing to ultrasonically disperse in an ice-water bath to dissolve the iron (III) chloride hexahydrate to form an iron (III) chloride hexahydrate-fluorinated graphene dispersion; Adding a reducing agent, a stabilizer and a surfactant to the iron (III) chloride hexahydrate-graphene fluoride dispersion in sequence, stirring and mixing evenly to form a mixed solution; The mixed solution is transferred into a high-pressure reactor for hydrothermal reaction. After the reaction is completed, the reaction product is subjected to magnetic separation and repeatedly washed and separated with anhydrous ethanol; The reaction product after magnetic separation is freeze-dried to obtain a composite material of magnetic Fe3O4 nanoparticles partially coated with fluorinated graphene.
9. The preparation method according to claim 8, characterized in that: The reducing agent and the stabilizing agent are one or more of anhydrous sodium acetate, anhydrous ammonium acetate, sodium citrate, and ascorbic acid; the surfactant is polyethylene glycol of different molecular weights, specifically one or more of Mn 2000, Mn 6000, Mn 4000, Mn 1000, and Mn 8000.
10. The preparation method according to claim 8 or 9, characterized in that: The hydrothermal reaction temperature is 200° C. to 220° C., and the reaction time is 24 h to 70 h.
Citation Information
Patent Citations
Preparation method of epoxy resin / GO super-hydrophobic anticorrosive coating
CN112409884A
Cited By
Preparation method of magnetic anti-corrosion functional filler
CN121673876A